Autonomous navigation on unmanned aerial vehicle (UAV) - Foo, Bryan Kai Xiang (2019)
This report documents the work of the author’s final year project over the duration of two semesters. This report focuses on comparing two path planners, Fast Marching Method (FMM) and A* search, on UAV also known as drone, that has the same complexity of O(N log N) and completeness. The use of Robot Operating System (ROS) helps the author simulate a drone in an environment, navigating its way to the end point. This report begins with a brief introduction about autonomous navigation, followed by literature reviews on path planners that are available and recognised in the world of autonomous navigation. Following which, the methodology of conducting the experiments and the results related to Unmanned Aerial Vehicle (UAV) autonomous navigation.